(untitled) (Research, Society and Development, 2025)
Diseases of the cardiovascular system (CSD) are the main cause of mortality in the world, being responsible for an average of 17.1 million deaths per year worldwide. Among CSDs, acute coronary syndrome stands out, which is characterized by obstruction of blood flow and can be characterized into three types, including acute myocardial infarction with ST elevation, which represents a significant threat to life, requiring rapid diagnosis and immediate intervention to reduce mortality and associated complications. Therefore, the study aimed to analyze the balloon door time of patients with acute myocardial infarction with ST-segment elevation. This is a quantitative, documentary, retrospective study, where the research was approved and released with opinion no. 7,041,945 by the Ethics and Research Committee of Atitus Educação and, also, by the hospital institution where the research was carried out, finding within the requirements of Resolution of the National Health Council No. 510, of April 7, 2016. When analyzing the data, it was found that 66% of patients were aged >55 years, were male, only 28% were from the municipality of Passo Fundo and in 88% of cases they had some comorbidity. The door-to-electrocardiogram time was within 10 minutes in 96% of cases and the door-to-balloon time was within 90 minutes in 68% of cases. It can be concluded that AMI cases are being managed, for the most part, in accordance with what is stipulated by the Brazilian Society of Cardiology.